Flexible non-burned decorative plate powder suitable for low-temperature roll forming and continuous preparation method of flexible non-burned decorative plate
Patent Information
- Application Number
- CN202610913600.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-24
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2046-06-24
AI Technical Summary
另外,在固化过程中需要排出软瓷中的水汽,容易在软瓷表面产生大量气孔,导致软瓷表面产生粉化,手感粗糙,且影响喷墨图案精度
(1)本发明采用干料热辊压的方式制备免烧柔性装饰板,先预制粉料,再连续热辊压,将制粉工艺与压制成型工艺分开,可以大幅提升生产效率。本发明克服了传统湿浆料注模养护周期长,产品表面缺陷多,质量不稳定、生产效率低的难题。
Smart Images

Figure CN122426959B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of building ceramics, and specifically relates to a flexible non-fired decorative panel powder suitable for low-temperature roll forming and a continuous preparation method for flexible non-fired decorative panels. Background Technology
[0002] Flexible ceramic tile is a new type of flexible and environmentally friendly decorative building material. It is made from natural minerals as the base material, combined with polymer additives, and processed using a low-temperature process. Flexible ceramic tile is widely used in building exterior walls, renovation and refurbishment, interior decoration, and curved surface shaping projects.
[0003] Currently, the common process for preparing flexible ceramics is a combination of slurry preparation, molding, and low-temperature curing or UV curing. Organic polymer emulsions are used to modify inorganic mineral raw materials, and additives are added to prepare a flexible ceramic slurry. This slurry is then injected into a mold and cured at 80-150℃ using thermosetting or UV curing. Afterward, demolding, pattern printing, coating, cutting, and packaging are performed. Existing processes require multiple steps of molding, curing, and demolding, resulting in low production efficiency. Flexible ceramic slurry contains a large amount of water, and the ceramics have a certain thickness. Due to the slow evaporation rate of water and the fact that UV light can only reach the surface of the ceramics, the low-temperature or UV curing speed is slow, requiring a considerable length of drying kiln section or UV curing tunnel. Furthermore, the conveyor belt speed of the mold carrying the ceramics in the curing section is very low, typically only 2-4 meters per minute. Some companies have adopted a combination of spray molding and continuous ring molds to increase production capacity; however, the speed limit in the curing section restricts capacity expansion. Even so, the output of a single automated industrial production line can only reach 1000-1500 square meters / 24 hours. Meanwhile, the demolding stage requires a large amount of manual labor for molding and demolding. In addition, during the curing process, moisture needs to be removed from the flexible ceramic, which can easily create a large number of pores on the surface of the flexible ceramic, causing the surface to powder, resulting in a rough feel and affecting the accuracy of inkjet patterns. Summary of the Invention
[0004] To address the aforementioned problems, this invention aims to develop a novel flexible non-fired decorative panel formulation system and preparation process, thereby improving the production quality and efficiency of flexible non-fired decorative panels. The term "flexible" refers to meeting at least the flexibility requirements of the JG / T 311-2011 standard.
[0005] One of the technical objectives of this invention is to provide a flexible, non-fired decorative panel powder formulation system suitable for low-temperature roll forming, improving the uniformity of the powder and thus enhancing product quality. The flexible, non-fired decorative panel powder of this invention comprises the following components (by weight): 50-66 parts inorganic stone powder, 10-20 parts inorganic aggregate, 0.5-1 part chopped fiber, 10-15 parts binder, 5-10 parts reinforcing agent, 3-5 parts modifier, 0.5-1.5 parts weather-resistant agent, and 0.5-1 part stabilizer; the binder is 80-120 mesh low-density polyethylene (LDPE) granules; the reinforcing agent is 80-120 mesh... The copolymer is polypropylene (copolymer PP); the modifier is ethylene-vinyl acetate (EVA) of 80-120 mesh; the weather-resistant agent is at least one of polyolefin elastomer of 80-120 mesh, 2-hydroxy-4-n-octyloxybenzophenone, and 2-(2'-hydroxy-3',5'-di-tert-butylphenyl)-5-chlorobenzotriazole; the stabilizer is pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] of 80-120 mesh.
[0006] Preferably, the inorganic stone powder is at least one of feldspar powder of 200-320 mesh, ceramic polishing waste powder, and calcite powder.
[0007] Preferably, the inorganic aggregate is at least one of 80-120 mesh natural sand and ceramic polishing waste.
[0008] Preferably, the chopped fiber material is at least one of chopped alumina fibers, chopped mullite fibers, and chopped glass fibers with a length of 0.04~0.08 mm.
[0009] The second technical objective of this invention is to provide a continuous manufacturing process for flexible decorative panels, separating the powder preparation process from the molding process to improve production efficiency. The continuous manufacturing method for the flexible, non-fired decorative panels includes the following steps: (1) According to the formula of the flexible non-fired decorative panel powder suitable for low temperature roll forming, mix the components evenly, then add the film-forming agent under stirring conditions, continue stirring until agglomeration occurs and no fine powder flows, stop stirring, and obtain flexible non-fired decorative panel mixture. (2) The mixture prepared in step (1) is aged, and after crushing and sorting, flexible non-fired decorative board mixed granules are obtained; (3) The mixed granules prepared in step (2) are pressed into shape by continuous hot rolling, and then the pattern layer is printed, the cover layer is prepared, and the granules are disassembled and packaged to obtain a flexible non-fired decorative board.
[0010] Preferably, in step (1), the film-forming agent is at least one of polyvinyl alcohol aqueous solution, carboxymethyl cellulose aqueous solution, and polyethylene oxide aqueous solution; preferably, the mass concentration of the film-forming agent is 1% to 3%; more preferably, the mass percentage of the film-forming agent in the flexible non-fired decorative board mixture is 7% to 10%.
[0011] Preferably, in step (2), the aging process involves standing for 3 to 5 hours.
[0012] Preferably, in step (2), the particle size of the mixed granules is 20-40 mesh.
[0013] Preferably, in step (3), the continuous hot rolling is performed by heating both the upper and lower surfaces simultaneously, with a hot rolling pressure of 5~10 MPa and a roller surface temperature of 105~165℃ (preferably 105~130℃, more preferably 110~130℃). In the system of the present invention, it is not necessary to reach the melting point of the copolymer polypropylene. By relying on the LDPE / EVA melt system for coating and using interfacial blending, rigidity and wear resistance can be improved. Within this temperature range, the low-temperature hot-melt characteristics are highlighted, achieving surface softening of the copolymer polypropylene and realizing physical blending reinforcement.
[0014] Preferably, in step (3), the cover layer is a transparent protective layer. More preferably, the cover layer has functions such as anti-slip, wear-resistant, antibacterial, tactile, and glossy properties.
[0015] Preferably, in step (3), the thickness of the flexible non-fired decorative panel is 3~8 mm.
[0016] Compared with the prior art, the present invention has the following beneficial effects: (1) This invention uses a dry material hot roller pressing method to prepare non-fired flexible decorative panels. The powder is pre-made and then continuously hot roller pressed, separating the powder making process from the pressing and molding process, which can greatly improve production efficiency. This invention overcomes the problems of long curing cycle, many surface defects, unstable quality and low production efficiency of traditional wet slurry injection molding.
[0017] (2) In this invention, inorganic stone powder, inorganic aggregate, short fiber and additives are mixed evenly first, then atomized film-forming agent is used for molding, and finally granulation is carried out. The prepared flexible non-fired decorative board mixed granules have high component uniformity and uniform particle size. The flexible non-fired decorative board pressed by hot roller has uniform thickness and stable performance.
[0018] (3) Flexible decorative panels prepared by traditional slurry injection molding and demolding processes have poor density, poor surface flatness, and are prone to powdering. This invention uses a continuous hot rolling process to prepare flexible non-fired decorative panels. Roller surfaces with mold-like effects can be used as needed to prepare decorative panels with mold-like effects on the surface or bottom. Because the roller pressing has greater pressure, the prepared flexible non-fired decorative panels have high density and even higher surface flatness. High-precision patterns and textures can be prepared by inkjet printing or high-uniformity coating can be prepared by spraying.
[0019] (4) The flexible non-fired decorative board prepared by the present invention has good flexibility, good water resistance, low temperature resistance, UV aging resistance, high surface density, and good anti-fouling performance. Attached Figure Description
[0020] Figure 1 The images show the surface effects of the sheet (left) and the flexible, non-fired decorative panel prepared by hot rolling according to Embodiment 1 of the present invention (right).
[0021] Figure 2 The images show the surface effects of the sheet (left) and the flexible, non-fired decorative panel prepared by hot rolling according to Embodiment 2 of the present invention (right).
[0022] Figure 3 These are images of the hot-rolled sheet (left) and the surface effect of the flexible non-fired decorative panel prepared in Embodiment 3 of the present invention (right).
[0023] Figure 4 This is a flexible display diagram of the flexible, fire-free decorative panel prepared in Embodiment 2 of the present invention.
[0024] Figure 5 This is a flexible display diagram of the flexible, non-fired decorative panel prepared in Comparative Example 3 of this invention. Detailed Implementation
[0025] The present invention is further illustrated by the following embodiments. It should be understood that the following embodiments are for illustrative purposes only and are not intended to limit the present invention.
[0026] Current flexible ceramic porcelain manufacturing processes suffer from two main problems: porosity is easily generated during slurry evaporation, and the surface of the flexible ceramic porcelain frequently becomes powdery, resulting in a rough feel and affecting the accuracy of inkjet patterns. Furthermore, the manufacturing process requires manual mold making, making continuous production impossible, leading to long production cycles and low output.
[0027] To address the aforementioned problems, this invention provides a flexible, non-fired decorative panel formulation suitable for low-temperature roll forming, comprising the following components: by weight, 50-66 parts of inorganic powder, 10-20 parts of inorganic aggregate, 0.5-1 part of chopped fiber, 10-15 parts of binder, 5-10 parts of reinforcing agent, 3-5 parts of modifier, 0.5-1.5 parts of weather-resistant agent, and 0.5-1 part of stabilizer.
[0028] The inorganic powder is at least one type of inorganic stone powder, such as feldspar powder, ceramic polishing waste powder, calcite powder, etc. The mesh size of the inorganic powder is 200-320 mesh. The ceramic polishing waste powder used as the inorganic powder is mainly generated by the friction between the diamond brush head and the ceramic surface during the fine polishing stage. The feldspar powder is selected from potassium feldspar powder and / or sodium feldspar powder.
[0029] The inorganic aggregate is at least one type of inorganic granular material, such as natural sand or ceramic polishing waste. The mesh size of the inorganic aggregate is 80-120 mesh. The ceramic polishing waste used as inorganic aggregate is primarily composed of particles with a relatively large particle size generated by friction between a diamond abrasive brush head and the ceramic surface during the coarse polishing stage. The natural sand includes, but is not limited to, water-jet sand, sodium silicate sand, and quartz sand.
[0030] The chopped fiber material is at least one of chopped alumina fibers, chopped mullite fibers, and chopped glass fibers with a length of 0.04~0.08 mm. The chopped fiber material can enhance the crack resistance of the flexible non-fired decorative panel. If the chopped fiber is too short, its effect on enhancing the crack resistance of the flexible non-fired decorative panel will be insufficient; if the chopped fiber is too long, it will lead to poor uniformity of the mixture in the flexible non-fired decorative panel.
[0031] The binder is low-density polyethylene granules of 80-120 mesh. Its main function is to impart flexibility and ductility to the flexible decorative panel, achieve low-temperature hot-melt molding, improve the adhesion between inorganic materials, ensure the finished product is crack-resistant, adaptable to curved surfaces, and does not produce harmful substances. If the binder particle size is too large, the hot-melt speed will be slower. If the binder particle size is too small, it will lead to uneven binder distribution and poorer melting and coating effect on the inorganic stone powder.
[0032] The reinforcing agent is 80-120 mesh copolymer polypropylene. The hot melt temperature (hot processing temperature, above the melting point) of the copolymer polypropylene is 155-168℃. Its main function is to improve the rigidity, weather resistance, and scratch resistance of flexible ceramics, and to improve the problems of fading and chalking after long-term outdoor use. Moreover, the blending of copolymer polypropylene with low-density polyethylene can balance flexibility and durability. If the particle size of the reinforcing agent is too large, it will not be able to melt-blend with the binder. If the particle size of the reinforcing agent is too small, the reinforcing effect will be poor.
[0033] Currently, commonly used polymeric additives for flexible ceramics include polyvinyl chloride (PVC) and polyethylene terephthalate (PET). PVC's hot melt / hot rolling temperature is 140-180℃. During the hot melt process, it is prone to decomposition, yellowing, and the release of toxic hydrogen chloride gas. Even with stabilizers, the release of toxic gases cannot be completely suppressed. PET's hot melt temperature is 260-280℃. This high temperature results in high energy consumption, and PET, being a rigid, weakly polar molecule, has low bonding strength with inorganic powders and organic components, making it prone to brittleness after cooling. This invention selects LDPE as the main resin and copolymerized PP as the reinforcing resin. The hot rolling temperature is low, and it precisely reaches the softening temperature of the copolymerized PP, thus forming physical reinforcement.
[0034] The modifier is 80-120 mesh ethylene-vinyl acetate. The hot melt temperature of ethylene-vinyl acetate is 90-120℃. Its main function is to improve the compatibility of the inorganic components of the resin, prevent delamination of the finished product, and lower the hot melt temperature, thus enhancing the low-temperature flexibility of the flexible decorative panel. If the particle size of the modifier is too large, it will not be able to melt-blend with the binder. If the particle size of the modifier is too small, it will cause agglomeration.
[0035] The weather-resistant additive is at least one of 80-120 mesh polyolefin elastomer (hot melt temperature 77-96℃), 2-hydroxy-4-n-octyloxybenzophenone (hot melt temperature 47-50℃), or 2-(2'-hydroxy-3',5'-di-tert-butylphenyl)-5-chlorobenzotriazole (hot melt temperature 150℃-153℃). The weather-resistant additive can improve the low-temperature resistance and UV aging resistance of the flexible, non-fired decorative panel.
[0036] The stabilizer is pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] at a mesh size of 80-120. The hot melt temperature of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] is 110-125℃. Hindered phenolic stabilizers are more effective for LDPE / PP. A calcium-zinc composite stabilizer, an environmentally friendly and non-toxic stabilizer with calcium stearate and zinc stearate as its main components, has also been used.
[0037] In summary, this invention has specifically selected the composition and proportion of binders, reinforcing agents, modifiers, weather-resistant additives, and stabilizers. The resulting flexible, non-fired decorative panel formulation is adapted to the low-temperature rolling temperature design, ensuring both the feasibility of the low-temperature rolling process and the performance of the product, which possesses excellent flexibility, alkali resistance, and surface quality.
[0038] In addition, the exemplary preparation method of the flexible non-fired decorative panel provided by the present invention includes the following steps: (1) Add each component of the flexible non-fired decorative board formula to the mixer and mix them evenly by stirring and vibration. Then, under the stirring condition, use an atomizing device to atomize the film-forming agent into the mixer and continue stirring until agglomeration occurs and no fine powder flows, and then stop to obtain the flexible non-fired decorative board mixture.
[0039] (2) After aging the mixture prepared in step (1) for a certain period of time, the mixture is crushed and sorted by air classifier to obtain flexible non-fired decorative board mixed granules.
[0040] (3) Add the mixed granules prepared in step (2) into the cloth feeding machine, press them into shape by continuous hot roller pressing, and then perform inkjet printing of pattern layer, preparation of cover layer, disassembly and packaging and other processes to obtain environmentally friendly flexible non-fired decorative board.
[0041] In step (1), the atomizing device has an orifice diameter of 0.5~0.8 mm, and the atomized droplets are micro-nano in size; the film-forming agent is at least one of polyvinyl alcohol aqueous solution, carboxymethyl cellulose aqueous solution, and polyethylene oxide aqueous solution; the mass concentration of the film-forming agent is 1%~3%; and the mass percentage of the film-forming agent in the flexible non-fired decorative board mixture is 7%~10%.
[0042] In step (2), the aging process is static setting, and the aging time is 3-5 hours; the air classifier crusher can control the particle size of the crushed material by adjusting the wind force; the particle size of the mixed granules is 20-40 mesh.
[0043] In step (3), the continuous hot roller pressing involves heating both the upper and lower surfaces simultaneously. A continuous roller press is used, with a pressure of 5-10 MPa. Too low a hot roller pressure will result in a loose preform with poor adhesion; too high a hot roller pressure will cause hot melt overflow. The roller surface temperature is 105-130℃, preferably 110-130℃. If the hot roller temperature is too low, the resin cannot melt into a continuous phase, failing to effectively encapsulate the inorganic raw materials, and will result in insufficient adhesion and powder shedding; if the hot roller temperature is too high, the resin will undergo excessive cross-linking, leading to thermal oxidation and decomposition.
[0044] In step (3), the inkjet printing is a continuous inkjet printing device; the ink is inorganic ink for ceramics or UV printing ink; the process of preparing the cover is spraying or hot rolling; the cover is a transparent protective layer, and the cover may have additional functions, such as anti-slip, wear-resistant, antibacterial, tactile, gloss, etc.; the thickness of the environmentally friendly flexible non-fired decorative board is 3~8 mm.
[0045] The following examples further illustrate the present invention in detail. It should also be understood that the following examples are only for further explanation of the present invention and should not be construed as limiting the scope of protection of the present invention. Any non-essential improvements and adjustments made by those skilled in the art based on the above description of the present invention are within the scope of protection of the present invention. The specific process parameters, etc., in the following examples are merely examples within a suitable range; that is, those skilled in the art can make appropriate selections within the appropriate range based on the description herein, and are not intended to be limited to the specific values in the examples below.
[0046] The chemical composition of the sodium carbonate in each embodiment includes, by mass percentage: IL 0.45%, SiO2 74.01%, Al2O3 15.75%, Fe2O3 0.12%, TiO2 0.06%, CaO 0.33%, MgO 0.07%, K2O 0.97%, Na2O 8.08%.
[0047] Examples 1-3 The preparation method of flexible non-fired decorative panels includes the following steps: (1) Add all components of the flexible non-fired decorative panel formula to a mixer and mix them evenly by stirring and vibration. Then, under stirring conditions, use an atomizing device to atomize the film-forming agent into the mixer, and continue stirring until agglomeration occurs and no fine powder flows out, thus obtaining the flexible non-fired decorative panel mixture. The atomizing device mentioned in step (1) has a nozzle diameter of 0.6 mm, and the atomized droplets are of micro-nano size. The film-forming agent is a polyvinyl alcohol aqueous solution with a mass concentration of 2%; the mass percentage of the film-forming agent in the flexible non-fired decorative panel mixture is 8%.
[0048] (2) After aging the mixture prepared in step (1) for 3 hours, the mixture is crushed and sorted using an air classifier to obtain flexible non-fired decorative panel mixed granules. The air classifier in step (2) controls the particle size of the crushed material by adjusting the air force. The particle size of the mixed granules is 30 mesh.
[0049] (3) The mixed granules prepared in step (2) are added to the fabric feeding machine and pressed into shape by continuous hot rolling. Then, inkjet printing of pattern layer, preparation of cover layer, disassembly and packaging and other processes are carried out to obtain flexible non-fired decorative board. The continuous hot rolling in step (3) is a continuous rolling press that heats the upper and lower bottom surfaces at the same time.
[0050] Table 1. Formulation of Flexible Non-fired Decorative Panels
[0051] Table 2. Manufacturing process parameters for flexible, non-fired decorative panels
[0052] Figure 1 The images show the surface effects of the hot-rolled sheet (left) and the flexible, non-fired decorative panel prepared in Example 1 of this invention (right). The results show that the flexible, non-fired decorative panel has a good simulated stone decorative effect.
[0053] Figure 2 These are images of the sheet (left) and the flexible, non-fired decorative panel prepared according to Example 2 of this invention, after hot rolling (right). The results show that the flexible, non-fired decorative panel has a good decorative effect on the surface of star and moonstone molds.
[0054] Figure 3 These are images of the hot-rolled sheet (left) and the flexible, non-fired decorative panel (right) prepared according to Example 3 of this invention. The results show that the flexible, non-fired decorative panel has a good decorative effect on the travertine surface.
[0055] Figure 4 This is a diagram illustrating the flexibility of the flexible, non-fired decorative panel prepared in Example 2 of this invention. The results show that the flexible, non-fired decorative panel possesses excellent flexibility.
[0056] Comparative Example 1 Weigh 100 parts of acrylic emulsion (50% solids content), 2 parts of defoamer (Elite YX-502C), 0.8 parts of wetting agent (German Corning, PE100), and 7 parts of film-forming aid dodecyl alcohol ester (Jiangsu Runtian Chemical). Stir and disperse at 250 rpm for 10 minutes. Then add 90 parts of 300-mesh ceramic polishing waste and 90 parts of white 200-mesh natural colored sand, and mix at 400 rpm for 15 minutes. During stirring, gradually add 15 parts of water to adjust the viscosity of the mixture until it can flow naturally and level. Pour the resulting slurry into a horizontally placed flat mold to a depth of 5 mm. After leveling, place the mold containing the slurry mixture in an 80℃ oven and bake for 5 hours. After cooling, demold to obtain flexible soft porcelain.
[0057] The performance tests for flexible, non-fired decorative panels are conducted in accordance with the relevant test methods and index requirements in JG / T 311-2011 Flexible Facing Bricks. The flexibility test method involves slowly bending the sample with its six faces facing outwards against the surface of cylinders with diameters of 120, 140, 160, 180, and 200 mm, observing for cracks on the sample surface. Flexibility is expressed as the smallest cylinder radius without cracks. Abrasion resistance is tested according to the relevant methods in JC / T 2219-2014 Modified Inorganic Powder Composite Building Facing Sheets, measured in abrasion value (750 r / g).
[0058] Table 3 Performance test results of flexible non-fired decorative panels
[0059] Comparative Example 2 The results were essentially the same as in Example 3, except that low-density polyethylene was replaced with copolymer PP. As a result, the roller surface temperature could not reach the melt temperature of the copolymer PP, preventing the organic components from effectively combining with the inorganic components, thus hindering molding.
[0060] Comparative Example 3 The results were essentially the same as in Example 3, except that the low-density polyethylene was replaced with copolymer PP, and the roller surface temperature was increased to 165°C. Although molding was possible, the higher rigidity of the copolymer PP led to bending cracks. Figure 5 It cannot form flexible soft ceramic sheets, and the hot-melt temperature is too high, which does not conform to the manufacturing concept of energy conservation and environmental protection.
[0061] Comparative Example 4 The process is essentially the same as in Example 3, except that the copolymer PP is replaced with low-density polyethylene. The result is a flexible and environmentally friendly decorative sheet, but it has poor rigidity, leading to insufficient wear resistance.
[0062] Comparative Example 5 The process is essentially the same as in Example 3, except that 4 parts of 100-mesh ethylene-vinyl acetate are removed, while 2 parts of 100-mesh low-density polyethylene and 2 parts of 80-mesh copolymer PP are added. Although a flexible and environmentally friendly decorative sheet can be prepared, peeling occurs on the sheet surface. This is because EVA enhances the bonding force between the resin and inorganic materials, and also prevents surface peeling caused by the temperature difference between the roller surface and the inside of the sheet.
[0063] Comparative Example 6 The process was essentially the same as in Example 1, except that the LDPE content was adjusted to 23 parts and the copolymer PP content to 2 parts. While a flexible and environmentally friendly decorative sheet could be produced, the excessively high LDPE content resulted in a severely plastic-like surface after hot-melting. Furthermore, the insufficient copolymer PP content led to inadequate abrasion resistance and strength of the sheet.
[0064] Comparative Example 7 The process was essentially the same as in Example 1, except that the LDPE content was adjusted to 5 parts and the copolymer PP content to 20 parts. The resulting sheet could not be molded due to the excessively low LDPE content.
[0065] Comparative Example 8 Similar to Example 1, the only difference was that ethylene-vinyl acetate was replaced with ethylene-acrylic acid copolymer (EAA) or chlorinated polyethylene (CPE) of type 135A. As a result, after replacing with EAA, the hot-melt temperature matched, but the water absorption rate of the prepared sheet increased, and the flexibility decreased. Because EAA has high rigidity after cooling, replacing EVA resulted in poorer flexibility of the finished product, making curved surfaces prone to cracking. After replacing with CPE, the surface of the prepared sheet exhibited peeling, mainly because CPE has poor compatibility with LDPE and poor hot-melt dispersion. In addition, hydrogen chloride gas was released during hot melting, resulting in a strong odor.
[0066] Comparative Example 9 Similar to Example 1, the only difference was that the modifier EVA was changed to 8 parts and the amount of copolymerized PP was changed to 7 parts. As a result, during the hot rolling process, the sheet stuck to the rollers, leading to a significant increase in the surface breakage rate of the sheet. The main reason was that the excessive amount of EVA caused the melt to be too thin during the hot melting process.
[0067] Comparative Example 10 Similar to Example 1, the only difference was that the stabilizer pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] was replaced with a calcium-zinc composite stabilizer. As a result, yellow spots appeared locally on the sheet surface, and the color difference was significant, leading to a substantial increase in the defect rate. The main reason was that the calcium-zinc composite stabilizer had low stability during continuous production, accumulating zinc soap and causing zinc burning, resulting in yellowing and localized scorching of the sheet. This defect was particularly noticeable during long-term production line operation.
[0068] Comparative Example 11 Similar to Example 1, the only difference is that LDPE is replaced with polyvinyl chloride (PVC), the stabilizer is replaced with 0.5 parts of 80-mesh pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] and 0.5 parts of calcium-zinc composite stabilizer, and the roller surface temperature is changed to 150°C. As a result, hydrogen chloride gas with a pungent odor is released during the preparation process. Although the calcium-zinc composite stabilizer is added, it cannot completely suppress the generation of hydrogen chloride. Furthermore, the roller surface temperature must reach 150°C, resulting in high energy consumption.
[0069] Comparative Example 12 Similar to Example 1, the only difference was that LDPE was replaced with polyethylene terephthalate (PET), the stabilizer was replaced with 0.5 parts of 80-mesh pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid] and 0.5 parts of calcium-zinc composite stabilizer, and the roller surface temperature was changed to 265°C. As a result, the pressed sheets suffered severe delamination and powdering, failing to form a complete shape. The main reason was that PET is a weakly polar material with extremely poor compatibility with stone powder and other polymeric materials. Furthermore, PET itself has high rigidity and poor deformation capacity, resulting in sheets with almost no flexibility.
[0070] In summary, compared to traditional slurry injection molding processes, the flexible decorative panels prepared by this invention exhibit significantly improved overall performance. These panels have lower water absorption, better flexibility, and significantly enhanced alkali resistance and aging resistance. More importantly, they overcome the challenges of surface porosity and pulverization inherent in traditional slurry processes.
Claims
1. A flexible, non-fired decorative panel powder suitable for low-temperature roll forming, characterized in that, It comprises the following components by weight: 50-66 parts inorganic stone powder, 10-20 parts inorganic aggregate, 0.5-1 part chopped fiber, 10-15 parts binder, 5-10 parts reinforcing agent, 3-5 parts modifier, 0.5-1.5 parts weather-resistant agent, and 0.5-1 part stabilizer; wherein the binder is 80-120 mesh low-density polyethylene granules; the reinforcing agent is 80-120 mesh copolymer polypropylene; the modifier is 80-120 mesh ethylene-vinyl acetate; the weather-resistant agent is at least one of 80-120 mesh polyolefin elastomer, 2-hydroxy-4-n-octyloxybenzophenone, and 2-(2'-hydroxy-3',5'-di-tert-butylphenyl)-5-chlorobenzotriazole; and the stabilizer is 80-120 mesh tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid]. Pentaerythritol ester; The continuous preparation method of flexible non-fired decorative panels includes the following steps: (1) According to the formula of the flexible non-fired decorative panel powder suitable for low temperature roll forming, mix the components evenly, then add the film-forming agent under stirring conditions, continue stirring until agglomeration occurs and no fine powder flows, stop stirring, and obtain flexible non-fired decorative panel mixture. (2) The mixture prepared in step (1) is aged, and after crushing and sorting, flexible non-fired decorative board mixed granules are obtained; (3) The mixed granules prepared in step (2) are pressed into shape by continuous hot rolling, and then the pattern layer is printed, the cover layer is prepared, and the granules are disassembled and packaged to obtain a flexible non-fired decorative board; the continuous hot rolling is to heat the upper and lower surfaces at the same time, using a continuous rolling press with a pressure of 5~10 MPa and a roller surface temperature of 105~130℃.
2. The flexible, non-fired decorative panel powder according to claim 1, characterized in that, The inorganic stone powder is at least one of 200-320 mesh feldspar powder, ceramic polishing waste powder, and calcite powder.
3. The flexible, non-fired decorative panel powder according to claim 1 or 2, characterized in that, The inorganic aggregate is at least one of 80-120 mesh natural sand and ceramic polishing waste.
4. The flexible, non-fired decorative panel powder according to claim 1, characterized in that, The chopped fiber material is at least one of chopped alumina fibers, chopped mullite fibers, and chopped glass fibers with a length of 0.04~0.08 mm.
5. A continuous preparation method for flexible, non-fired decorative panels, characterized in that, The preparation method includes the following steps: (1) According to the formulation of the flexible non-fired decorative panel powder suitable for low temperature roll forming according to any one of claims 1 to 4, the components are mixed evenly, and then a film-forming agent is added under stirring conditions. Stirring is continued until agglomeration occurs and no fine powder flows. Stirring is stopped to obtain the flexible non-fired decorative panel mixture. (2) The mixture prepared in step (1) is aged, and after crushing and sorting, flexible non-fired decorative board mixed granules are obtained; (3) The mixed granules prepared in step (2) are pressed into shape by continuous hot rolling, and then the pattern layer is printed, the cover layer is prepared, and the granules are disassembled and packaged to obtain a flexible non-fired decorative board; the continuous hot rolling is to heat the upper and lower surfaces at the same time, using a continuous rolling press with a pressure of 5~10 MPa and a roller surface temperature of 105~130℃.
6. The preparation method according to claim 5, characterized in that, In step (1), the film-forming agent is at least one of polyvinyl alcohol aqueous solution, carboxymethyl cellulose aqueous solution, and polyethylene oxide aqueous solution; the mass concentration of the film-forming agent is 1% to 3%; and the mass percentage of the film-forming agent in the flexible non-fired decorative board mixture is 7% to 10%.
7. The preparation method according to claim 5 or 6, characterized in that, In step (2), the aging process involves standing for 3 to 5 hours.
8. The preparation method according to claim 5, characterized in that, In step (2), the particle size of the mixed granules is 20~40 mesh.
9. The preparation method according to claim 5, characterized in that, In step (3), the thickness of the flexible non-fired decorative panel is 3~8 mm.
Citation Information
Patent Citations
Inorganic artificial marble, and preparation method and application thereof
CN103396079A
Ultrafine silicate high-filled polyolefin wallpaper base paper and production method thereof
CN105196666A